Strength training combined with high-intensity interval aerobic trainingin young adults’ body composition - Alves, Ana Ruivo; Marinho, Daniel Almeida; Pecêgo, Marco; Ferraz, Ricardo; Marques, Mario Cardoso; Neiva, Henrique Pereira (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Although health-enhancing effects of physical activity are well-reported, a high rate of physical inactivity worldwide is still observed. Additionally, the most effective method for weight control and/or weight loss is still unknown. In this sense, analyzing whether strength training could be useful when combined with high-intensity aerobic interval training to improve body composition is important to provide further knowledge of the effects of combined strength and aerobic training in young adults. Aim of Study. The purpose of the study was to compare the effects of high-intensity interval aerobic training (HIIT) with a combined strength training followed by HIIT (ST+HIIT) on body composition of young adults. Material and Methods. Eighteen college students (age 24.83 ± 6.60 years, body mass 70.05 ± 14.26 kg, height 1.72 ± 0.08 m) were subjected to two different training programs for 8 weeks: high-intensity interval aerobic training (n = 9), or strength training combined with high-intensity interval aerobic training in the same session (n = 9). Anthropometric variables were assessed. Results. After eight weeks significant differences were found in body fat mass (p = 0.01; ES = 1.11), waist circumference (p = 0.04; ES = 0.82) and hip circumference (p = 0.04; ES = 0.82) with a large effect size in the ST+HIIT group. A large decrease in fat-free mass was found in the HIIT group (p = 0.04; ES = 0.80). Conclusions. These findings suggest that strength training should be added to high-intensity interval aerobic training to improve body composition in adults by reducing body fat after 8 weeks. Performing HIIT seems to contribute to the loss of fat-free mass. These outcomes might be important for physical fitness professionals and researchers, providing further understanding of the dose-response effects of combined strength and aerobic training in young adults.
Keywords: exercise; morphology; body fat; HIIT; health